Identifying Risk-Efficient Crop Portfolios for Different Cropping Systems by Analyzing the Tradeoffs Between Arable Farming Profits and Profit Stability - Pergner, Isabell; Lippert, Christian (German Journal of Agricultural Economics, 2025)
As in agriculture uncertainties have increased due to extreme weather events and yield variations, a critical examination of crop rotation strategies is needed. This study analyses the relationship between risk and crop rotation planning, addressing the challenges posed by an increasing yield variability and related total contribution margin fluctuations. For the systems ‘conventional farming’, ‘organic farming’ and ‘farming without pesticides, but with mineral fertilizer’ time series data of crop yields, prices and variable costs are collected. The data is used for a Monte Carlo simulation that yields average contribution margins for the considered crops and their (co-)variances, which are needed to build a hypothetical model farm. Relying upon Quadratic Risk Programming, the expected total contribution margins are maximized for a set of fixed total contribution margin variances. Efficient frontiers are derived that show respective optimum combinations of the expected value of the total contribution margin and its standard deviation. Organic farming shows high average total contribution margins for optimized crop rotations, but also increased variance compared to other cropping systems. The inclusion of cereals in a crop rotation lowers the risk, whereas the inclusion of potatoes and sugar beet increases the risk within a crop portfolio across all systems. Optimizing and diversifying the crop portfolio for each cropping system is essential. An optimized farming system without pesticides, but with mineral fertilizer exhibits lower risk but also lower total contribution margin compared to other systems. This is due to a different crop portfolio but also to relatively low prices and yields.